Circulating heat shock protein 70 (HSPA1A) in normal and pathological pregnancies - Molvarec, Attila (Springer Netherlands, 2009)
Heat shock proteins (Hsps) are ubiquitous and phylogenetically conserved molecules. They are usually considered to be intracellular proteins with molecular chaperone and cytoprotective functions. However, Hsp70 (HSPA1A) is present in the peripheral circulation of healthy nonpregnant and pregnant individuals. In normal pregnancy, circulating Hsp70 levels are decreased, and show a positive correlation with gestational age and an inverse correlation with maternal age. The capacity of extracellular Hsp70 to elicit innate and adaptive proinflammatory (Th1-type) immune responses might be harmful in pregnancy and may lead to the maternal immune rejection of the fetus. Decreased circulating Hsp70 level, consequently, may promote the maintenance of immunological tolerance to the fetus. Indeed, elevated circulating Hsp70 concentrations are associated with an increased risk of several pregnancy complications. Elevated Hsp70 levels in healthy pregnant women at term might also have an effect on the onset of labor. In preeclampsia, serum Hsp70 levels are increased, and reflect systemic inflammation, oxidative stress and hepatocellular injury. Furthermore, serum Hsp70 levels are significantly higher in patients with the syndrome of hemolysis, elevated liver enzymes, and low platelet count (HELLP syndrome) than in severely preeclamptic patients without HELLP syndrome. In HELLP syndrome, elevated serum Hsp70 level indicates tissue damage (hemolysis and hepatocellular injury) and disease severity. Increased circulating Hsp70 level may not only be a marker of these conditions, but might also play a role in their pathogenesis. Extracellular Hsp70 derived from stressed and damaged, necrotic cells can elicit a proinflammatory (Th1) immune response, which might be involved in the development of the maternal systemic inflammatory response and resultant endothelial damage in preeclampsia and HELLP syndrome. Circulating Hsp70 level is also elevated in preterm delivery high-risk patients, particularly in treatment-resistant cases, and may be a useful marker for evaluating the curative effects of treatment for preterm delivery. In addition, increased circulating Hsp70 levels observed in asthmatic pregnant patients might play a connecting role in the pathomechanism of asthmatic inflammation and obstetrical/perinatal complications. Nevertheless, a prospective study should be undertaken to determine whether elevated serum Hsp70 level precedes the development of any pregnancy complication, and thus can help to predict adverse maternal or perinatal pregnancy outcome. Moreover, the role of circulating Hsp70 in normal and pathological pregnancies is not fully known, and further studies are warranted to address this important issue.